IMPROVING THE STUDENTS’ VOCABULARY MASTERY’ USING GAMES INVOLVING PICTURES IN ELEMENTARY SCHOOL - ira ida yustina (STKIP PGRI Lubuklinggau, 2019)
The objectives of the study are to describe and find out the effectiveness the teaching of English vocabulary using games involving pictures in class activities at the third grade students of Elementary School. This study is action research. The subject of study is the third grade students of Elementary School of Piri Nitikan Yogyakarta. There were 17 students in the class. The data were collected from the observation, interview and test. The data were analyzed from field notes, interview transcript, the observation sheets and test result. It is concluded that using games involving picture in the class can make some progress to the students. The students can increase their vocabulary mastery and their ability both in writing words and in speaking. The students can pronounce the English words correctly. Besides, using games involving picture make the students active and enjoy English class.